Supporting safe and gradual reduction of long‐term benzodiazepine receptor agonist use: Development of the SAFEGUARDING‐BZRAs toolkit using a codesign approach. (7th June 2022) - Lynch, Tom; Ryan, Cristín; Bradley, Colin; Foster, D.; Huff, Christy; Hutchinson, Sharon; Lamberson, Nicole; Lynch, Lily; Cadogan, Cathal
Abstract: Introduction: Long‐term benzodiazepine receptor agonist (BZRA) use persists in healthcare settings worldwide and poses risks of patient harm. Objective: This study aimed to develop an intervention to support discontinuation of long‐term BZRA use among willing individuals. Methods: The intervention development process aligned with the UK Medical Research Council's complex intervention framework. This involved a previous systematic review of brief interventions targeting long‐term BZRA use in primary care and qualitative interviews based on the Theoretical Domains Framework that explored barriers and facilitators to discontinuing long‐term BZRA use. A codesign approach was used involving an active partnership between experts by experience, researchers and clinicians. Intervention content was specified in terms of behaviour change techniques (BCTs). Results: The SAFEGUARDING‐BZRAs (Supporting sAFE and GradUAl ReDuctIon of loNG‐term BenZodiazepine Receptor Agonist uSe) toolkit comprises 24 BCTs and includes recommendations targeted at primary care‐based clinicians for operationalizing each BCT to support individuals with BZRA discontinuation. Conclusion: The SAFEGUARDING‐BZRAs toolkit has been developed using a systematic and theory‐based approach that addresses identified limitations of previous research. Further research is needed to assess its usability and acceptability by service users and clinicians, as well as its potential to effectively support safe and gradual reduction of long‐term BZRA use. Patient or Public Contribution: The qualitative interview phase included patients as participants. The codesign process included 'experts by experience' with either current or previous experience of long‐term BZRA use as collaborators.